High-speed copper bromide laser monitors - Evtushenko G. S. Gennady Sergeevich; Gubarev F. A. Fedor Aleksandrovich; Sukhanov V. B. Viktor Borisovich; Trigub M. V. Maksim Viktorovich; Torgaev S. N. Stanislav Nikolaevich (2009, 2009)
В фонде НТБ ТПУ отсутствует